Challenges of Self-Created Goodwill From Resource-Based View Theory in China - Wang, Yilin (2009)
Recognized as a unique economic resource of a corporation, goodwill has considerable influence on both earnings and future development. However, certain issues, e.g. how to define the nature of goodwill, and how to measure goodwill are still pending. Nowadays, goodwill is increasing its proportion in gross assets of a corporation, and the raising of mergers and acquisitions activities between corporations brings a great number of purchased goodwill to the scene, while such purchased goodwill originates from the self-created goodwill accumulated inside corporations. Therefore, it is safe to say the measurement of goodwill has remarkable significance. However self-generated goodwill has certain characteristics e.g. impartibility, risky and etc, such characteristics make the accurate measurement of goodwill relatively difficult. This article will discuss internally-generated based on the theory of the Resource Based View of the Firms and carried out in-depth discussions on the nature, recognition and measurement. The article considers self-created goodwill is a value embodiment of particular intangible assets and corporate capabilities which function on the basis of corporate assets so as to increase a value of corporation. Since the nature of self-created goodwill does not fit in the definition of asset while it is essential to the users of accounting information, therefore the article suggests that self-created goodwill should be reflected in accounting information by the means of off-balance sheet disclosure. Hence the article focused its discussions on the measurement of internally-generated goodwill. In respect of the nature of self-created goodwill prescribed by Resourced-based View, the value of self-created goodwill changes along with the changing of industry environment and corporate business standing, the traditional methods are not good enough to reflect self-created goodwill’s feature of dynamic change. The article agrees with applying the option theory to the evaluation of self-created goodwill. In the measurement of goodwill, corporate equity is considered the call options based on a corporation’s gross value, and value of equity is calculated by Black-Scholes option pricing model, then residuum approach will be applied to get the value of self-created goodwill by the difference between the gross market value of a public company’s shares and its equity value. This article will use a case study to solve the question of measuring self-created goodwill.